2015
DOI: 10.1016/j.jaac.2015.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Behavior Problems and Academic Outcomes in Adolescence: Longitudinal Population-Based Study

Abstract: Across the full range of scores at a population level, each 1-point increase in inattention at age 7 years is associated with worse academic outcomes at age 16. The findings highlight long-term academic risk associated with ADHD, particularly inattentive symptoms. After adjusting for inattention and ADHD respectively, oppositional/defiant behaviors and DBDs are also independently associated with worse academic outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
86
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(92 citation statements)
references
References 40 publications
5
86
0
1
Order By: Relevance
“…For children meeting all nine inattention criteria the effect size was 0.9 for English and mathematics, on average. The linear relationship between the number of inattention criteria met and academic attainment echoed the findings of Sayal et al (2015), which used the DAWBA to assess behaviour at age 7 and followed the children up to the end of secondary school. The present study used a substantially larger sample and showed that this pattern of later risk of negative outcomes can be identified in children as young as five years and, as such, has potentially important implications for education.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…For children meeting all nine inattention criteria the effect size was 0.9 for English and mathematics, on average. The linear relationship between the number of inattention criteria met and academic attainment echoed the findings of Sayal et al (2015), which used the DAWBA to assess behaviour at age 7 and followed the children up to the end of secondary school. The present study used a substantially larger sample and showed that this pattern of later risk of negative outcomes can be identified in children as young as five years and, as such, has potentially important implications for education.…”
Section: Discussionmentioning
confidence: 68%
“…The sample size of the six studies analysed by Duncan et al was not as large as the present study and the outcome measures were different between studies. Probing the association between behavior and academic outcomes, Sayal, Washbrook and Propper (2015) analysed a population-based sample of 11,640 students whose behavior was assessed by parents and teachers at the age of 7 using the Developmental and Wellbeing Assessment (DAWBA) and followed them up to the end of compulsory secondary education in England. The DAWBA provided scores for inattention and hyperactivity/impulsivity on a continuum which allowed the authors to investigate academic outcome for the full range of behaviours from no symptoms through to severe.…”
Section: Association's Diagnostic and Statistical Manual Of Mental DImentioning
confidence: 99%
See 1 more Smart Citation
“…Another large longitudinal population based follow-up study from England showed that every one-point increase in inattention symptoms at age 7 was associated with incrementally worse academic outcomes at age 16 as measured by standardized achievement tests. In boys, ADHD was associated with more than double the likelihood of not achieving acceptable scores across the range of subjects tested [26]. The chronic educational underachievement associated with ADHD has been demonstrated to have long-term implications for children's future health, socioeconomic, and employment outcomes [9,11,[27][28][29][30].…”
Section: Impact Of Adhd On School Performancementioning
confidence: 99%
“…[1][2][3] Children with behavioral problems enter kindergarten disadvantaged in language, motor, social, and school readiness skills and are at increased risk of poor longterm academic outcomes. 4,5 Behavioral problems are also associated with increased risk of substance abuse, anxiety disorders, ADHD, and suicide. 1,6 Furthermore, children with behavioral problems are at increased risk of harsh parenting and physical abuse.…”
Section: Introductionmentioning
confidence: 99%